ANOMALOUS PHASES EXCEEDING 90° IN MAGNETOTELLURICS: ANISOTROPIC MODEL STUDIES AND A FIELD EXAMPLE - Heise W.; Pous J. (My University, 2003)
A study of synthetic anisotropic models that explain phases exceeding 90° in magnetotellurics is presented. The basic model comprises an anisotropic layer overlain by a shallow (local) anisotropic block, with both structures inserted in a 2-D model. The 2-D strike and the anisotropy strikes (layer and block) differ. The influence of the following parameters was analysed: anisotropy strike, geometry of the block and the layer, and anisotropy ratios of the block and the layer. We show that, according to this model, the anomalous phase effect is limited to those sites above the shallow block and does not influence the regional structure, which can therefore be recovered. These results were applied to field data from a magnetotelluric profile in SW Iberia where phases greater than 90° occurred in an area in which alternating bands of schist and graphite-rich blackschists crop out, giving rise to strong macroanisotropy.
Keywords: anisotropy; electrical conductivity; magnetotellurics; phases